Alrighty, brace for a complete mess; I have no idea how to use LaTex.
let S = x + 2x^2 + 3x^3 + ... + nx^n
now, xS = x^2 + 2x^3 + 3x^4 + ... + (n - 1)x^n + nx^(n+1)
subtracting xS from S, we get
S - xS = x + 2x^2 + 3x^3 + 4x^4 + ... + nx^n - (x ^2 + 2x^3 + 3x^4 + ... + (n - 1)x^n) - nx^(n+1)
after collecting like terms, we get
(1 - x)S = x + x^2 + x^3 + ... + x^n - nx^(n+1)
using the result from i. ,
(1 - x)S = x(x^n - 1)/(x -1) - nx^(n+1)
dividing through by (1 - x)
so S = x^(n + 1) - x/(x -1)(1 - x) - nx^(n+1)/(1 - x)
flipping the sign of the (1 -x) in the denominator,
S = nx^(n+1)/(x-1) - x^(n + 1)/(x - 1)^2 + x/(x - 1)^2
= [ n(x-1)x^(n+1) - x^(n+1) + x ]/(x - 1)^2
= [ nx^(n+2) - (n+1)x^(n+1) + x ] /(x-1)^2
therefore, x + 2x^2 + 3x^3 + ... + nx^n = [nx^(n + 2) - (n + 1)x^(n+1) + x]/(x-1)^2
just check my working, i may have made a mistake lol.